THE IMPACT OF MARKETPLACE SIMULATIONS ON STUDENTS' ENTERPRENEURIAL COMPETENCES - Mariusz Pyra (Rozprawy Społeczne)
Abstract The objective of this paper is to identify the role and impact of Marketplace computer simulations on students’ competences in the field of entrepreneurship acquired in the process of studying at higher-education facilities. This paper draws on the literature describing the theory of entrepreneurial competences, and contains a presentation of the empirical research carried out in the course of learning.